2013
DOI: 10.1371/journal.pone.0083473
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in White Matter Microstructure as Vulnerability Factors and Acquired Signs of Traffic Accident-Induced PTSD

Abstract: It remains unclear whether white matter (WM) changes found in post-traumatic stress disorder (PTSD) patients are stress-induced or precursors for vulnerability. The current study aimed to identify susceptibility factors relating to the development of PTSD and to examine the ability of these factors to predict the course of longitudinal PTSD. Sixty two victims who had experienced traffic accidents underwent diffusion tensor imaging using a 3.0T MRI system within 2 days after their accidents. Of these, 21 were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 50 publications
3
29
0
Order By: Relevance
“…Laboratory stressors are hampered in their limited generalizability to real world challenges; however the stressor task utilized in this study evokes frustration and cognitive challenge, which are similar to many stressful experiences SZ would experience in everyday life. Overall, our finding of a correlation between reduced FA with prolonged cortisol reactivity is consistent with previous reports that chronic stress is associated with WM lesions (34) and reduced FA (57), and supports the a priori hypothesis that poor resolution of cortisol responses could cumulatively lead to WM alterations.…”
Section: Discussionsupporting
confidence: 92%
“…Laboratory stressors are hampered in their limited generalizability to real world challenges; however the stressor task utilized in this study evokes frustration and cognitive challenge, which are similar to many stressful experiences SZ would experience in everyday life. Overall, our finding of a correlation between reduced FA with prolonged cortisol reactivity is consistent with previous reports that chronic stress is associated with WM lesions (34) and reduced FA (57), and supports the a priori hypothesis that poor resolution of cortisol responses could cumulatively lead to WM alterations.…”
Section: Discussionsupporting
confidence: 92%
“…63 Also, in a prospective imaging study, lower FA and higher MD of vmPFC white matter (measured within 2 days posttrauma) predicted PTSD development at 1 and 6 months posttrauma. 16 Alternatively, lower uncinate fasciculus tract integrity in patients with…”
Section: Discussionmentioning
confidence: 99%
“…13 Moreover, vmPFC white matter integrity measured within 2 days posttrauma was lower in trauma-exposed individuals in whom PTSD developed compared with those who did not develop PTSD at 1 and 6 months posttrauma. 16 Regarding the cingulum bundle, lower white matter integrity of the cingulum (i.e., connecting the cingulate cortex with the hippocampus and amygdala) 17 has been observed in female patients with PTSD compared with trauma-exposed controls, possibly underlying impaired fear extinction learning. 14 However, according to a recent meta-analysis on 7 whole-brain DTI studies in patients with PTSD, increased FA of the cingulum bundle has also been observed in patients with PTSD.…”
Section: J Psychiatry Neurosci 2017;42(5)mentioning
confidence: 99%
“…41 Future directions potentially include the use of automated tract identification to evaluate the disease trajectory, 40,4244 modulate radiation therapy 42 or evaluate the response to therapy in patients with gliomas. 45,46 Finally, the integrity of white matter tracts is increasingly being applied in the clinical neurosciences as a biomarker of injury in a range of diseases from traumatic brain injury 47 to early Alzheimer's disease. 48 The ability to use automated, probabilistic methods, has been shown to be more reliable than manual determinations by individual experts, 49,50 as substantiated by the current report.…”
Section: Discussionmentioning
confidence: 99%